Assessment of Sequelae of Untreated Dental Caries using PUFA index in Children Visiting a Tertiary Center in Kathmandu - Khanal, Sanskriti; Shah, Priyanka; Khapung, Anju (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Dental caries is still a major health problem in most countries as it affects school aged children and adults also. Dental caries continues to be a major public health problem, especially in low and middle- income countries. It can be prevented and treated with proper utilization of dental services. Untreated dental caries can have pain and infection with significant impact on general health. Method: This study was conducted to assess the untreated dental caries in children using the pufa/PUFA index. A hospital based cross sectional study was carried out in 297 children aged 2-12 years old. Caries status was assessed by dmft/DMFT index and untreated caries by pufa/PUFA index. Results: The “untreated caries PUFA ratio” of the population was 30.69%. The mean dmft index was 5.51+3.59, mean pufa 1.39+1.48 and mean DMFT 0.43+1.03 mean PUFA 0.11+0.46 respectively for primary and permanent teeth. Primary dentition had more caries and pufa score than the permanent teeth. Conclusion: There were untreated caries present in the children showing lack of timely utilization of dental services.